The Role of Astrocytes in the Neurorepair Process - Chiareli, Raphaela Almeida; Carvalho, Gustavo Almeida; Marques, Bruno Lemes; Mota, Lennia Soares; Oliveira-Lima, Onésia Cristina; Gomes, Rodrigo Mello; Birbrair, Alexander; Gomez, Renato Santiago; Simão, Fabrício; Klempin, Friederike; Leist, Marcel; Pinto, Mauro Cunha Xavier (Frontiers in Cell and Developmental Biology, 2021)
Astrocytes are highly specialized glial cells responsible for trophic and metabolic support of neurons. They are associated to ionic homeostasis, the regulation of cerebral blood flow and metabolism, the modulation of synaptic activity by capturing and recycle of neurotransmitters and maintenance of the blood-brain barrier. During injuries and infections, astrocytes act in cerebral defense through heterogeneous and progressive changes in their gene expression, morphology, proliferative capacity, and function, which is known as reactive astrogliosis. Thus, reactive astrocytes release several signaling molecules that modulates and contributes to the defense against injuries and infection in the central nervous system. Therefore, deciphering the complex signaling pathways of reactive astrocytes after brain damage can contribute to the neuroinflammation control and reveal new molecular targets to stimulate neurorepair process. In this review, we present the current knowledge about the role of astrocytes in brain damage and repair, highlighting the cellular and molecular bases involved in synaptogenesis and neurogenesis. In addition, we present new approaches to modulate the astrocytic activity and potentiates the neurorepair process after brain damage.